Töre (törö) – the law of the ancient kyrgyz (about the origin and meaning of the term) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article studies the ancient legal system of the Kyrgyz and the Kyrgyz Kaganate in the 6th-10th centuries based on customary law - tore, natural law that arose due to objective necessity. Historically, customary law developed in the process of long and monotonous observance of certain norms and rules, which personified the legal views prevailing in society. It was regularity that transformed unwritten norms of behavior into actual law that regulated a wide range of relations. Based on rich written historical sources and research by scientists, the origin of the term “tore” is studied, the function of some officials who were in charge of order and legality in the state.
Keywords: töre, yosun, law, customary law, Kyrgyz, Kyrgyz Kaganate, runic.